Implementation of GIS techniques in mapping the characteristics of Temperah and Tui river’s catchment - Nurul Farhana, Ab Manaf (2015)
Tui River’s catchment and Temperah River’s catchment are located in Lipis District, Pahang. In 2013, the flash floods occur in several villages. It was because the mining activities near the area, causing Tui River overflow quickly when there is heavy rainfall. It was also due to the blockage of drainage. It causes a lot of damages to houses and structures. Some of residences submerged due to flood as examples some population places near to Temperah River are Kampung Kembuai, Kampung Paya Bah, Kampung Paya Tada and Kampung Temperah. During flood, residents moved to evacuation centres for flood victims. Flood destroys the property and structures that cause residents suffered losses. Implementation of Geographic Information System (GIS) techniques in mapping the characteristics of Temperah and Tui River’s catchment was a process to identify the characteristics of the catchments as a first step of flood mitigations project. The objectives of this research were mapping the area and land used in Tui River’s catchment and Temperah River’s catchment by using Geographical Information System (GIS) and identify the characteristics at Tui River’s catchment and Temperah River’s catchment, Lipis. This research was important to give initial information of characteristics of catchment to the local authorities such as Department of Irrigation and Drainage. The catchments was mapped using ArcMap 9.3 version. The characteristics of catchment that have been considered were the type of land use, type of soil in the catchment and the elevation of the catchments. Based on the result, the type of soil for both catchment were sandy clay loam, clay loam, silt loam and mining land which are medium soil in term of proportion of particles. They also have very low infiltration rates when thoroughly wetted. That is why some flood mitigation projects need to be done to overcome flood problem